Using facial-submental artery island flap and titanium plate to repair the defect following marginal resection for stage 3 medication-related osteonecrosis of the mandible - Wei-qi Cheng; Kai-fang Yuan; Wei-liang Chen (Asian Journal of Surgery, 2025)
Objective: To evaluate the feasibility of using a facial-submental artery island flap (FSAIF) combined with a titanium plate to repair defects after marginal resection. Patients and methods: Twenty-four patients with stage 3 medication-related osteonecrosis of the mandible (MRONM) underwent FSAIF combined with titanium to repair defects after margin resection. Postoperative complications were scored using the Clavien–Dindo classification system. The University of Washington Quality of Life Questionnaire (UW-QOL) was used to evaluate pain before and after surgery. Treatment efficacy was evaluated based on the UW-QOL pain score and fistula closure. Results: The median size of the skin paddle was 3.0 cm × 10.3 cm, and the total success rate was 95.8 %. Clavien–Dindo classification grades of I, II, and IIIb were assigned to 58.3 %, 37.5 %, and 4.2 % of the cases, respectively. Pre- and postoperative UW-QOL pain scores of 0, 25, 50, 75, and 100 were observed in 16.7 % and 0, 58.3 % and 4.2 %; 16.7 % and 8.3 %, 8.3 % and 33.3 %; and 0 and 54.2 % of cases, respectively, with significant differences seen between the pre- and postoperative scores (P < .001). The median follow-up duration was 18.4 months. The complete control rate was 54.2 %, the nearly completely control rate was 33.3 %, the partial control rate was 8.3 %, and the little-to-no control rate was 4.2 %. Of the participants, 83.3 % are alive without evidence of MROM or tumor recurrence. Conclusions: An FSAIF combined with a titanium plate implant for repairing MRONM in stage 3 cancer patients after mandibular margin resection achieved good results, and the technique is reliable and safe.